Energy security in times of economic transition : lessons from China - Lixia, Yao (Emerald Publishing Limited, 2021)
As China has shifted from a planned to a market-oriented economy, it has adjusted its energy policies accordingly. As a result, the Chinese energy industry has now gone through more than seventy years of transformation. Yet to date no single work has sought to assess the key factors driving these changes and their effects on China's energy security, even though such questions have implications for assessments of the world's energy security. Energy Security in Times of Economic Transition addresses this gap. Juxtaposing a domestic perspective with a wider, pan-energy-industry view, Yao Lixia explores trends in the evolution of China's energy policy since its inception in 1949 and discusses the relations between policy changes and macroeconomic reforms. Then, by employing a new, ground-breaking quantitative framework for evaluating energy security, Yao crucially shows that macroeconomic reform did not improve China's energy security over the first three decades of the reform period but in fact restricted China from developing more effective energy policies. This insight ultimately suggests lines of inquiry that can be extended to research in other countries, especially those in the midst of economic transition. For its detailed history of China's energy policy and its novel, widely applicable methodology for evaluating energy security, this book is a must-read for researchers and postgraduate students in economics, security studies, political economy, and international political economy.
Includes index.
Keywords: Energy security -- China.; China -- Economic conditions.; Business & Economics -- Industries / Energy.; Energy industries & utilities.; elektronické knihy; electronic books